THE INFLUENCE OF FINANCIAL CONFIDENCE, FINANCIAL SOCIALIZATION, HERDING, AND MENTAL ACCOUNTING ON INVESTMENT DECISION AMONG GENERATION Z IN JAKARTA - Angela, Della; Wiyanto, Hendra; Budiono, Herlina (International Journal of Application on Economics and Business, 2023)
This research purpose is to examine the influence of financial confidence, financial socialization, herding, and mental accounting on investment decision among Generation Z in Jakarta. The samples for this research are investors who were born between 1995-2010 (Generation Z) and living in Jakarta. The cluster sampling method was used to collect 205 respondents from a survey that was shared online on social media through google forms. The data of this research is analyzed through the use of a structural equation system using the SmartPLS.3.2.9 program. The result of this research shows that the investment decision of Gen Z investors in Jakarta is significantly influenced by financial confidence, financial socialization, herding, and mental accounting. This research also found that a lower frequency of trading which happens in Gen Z investors tends to overcome the negative impact of herding.